Quelle évolution de la place des femmes dans la culture héroïque centraméricaine ? - Catherine Lacaze (Caravelle)
The main hypothesis of this work is that national heroes have been for a long time a tool for the dissemination of dominant masculinity and the legitimisation of the patriarchal order established in Central America since the proclamation of independence in 1821. In the first part, breaks and continuities in the evolution of the heroic models are examined, and the place of women in the official narrative is determined. The third and last part looks at current issues of the links between history and gender.